OPTIMIZATION STUDY OF LEAD-FREE CS2SNI6 ADDITION INTO THE STRUCTURE OF DYE SENSITIZED SOLAR CELL (DSSC) AND ITS PERFORMANCE ENHANCEMENT - Tani Dosi, Amaldeus
Dye Sensitized Solar Cell (DSSC) technology has become considerable research in the last two decades in the field of energy conversion. DSSC is one of the most promising types of solar cells among third generation solar cells due to the ease of fabrication process. Several studies have been conducted to improve DSSC performance, for example by modifying the structure of DSSC or by adding perovskite materials and metal nanoparticles. Currently, there are many studies on the application of tin-based perovskite (Sn) to replace lead-based perovskite (Pb) because the Pb is toxic, and it has negative impact on the environment. It has been known that Cs2SnI6 perovskite material is more stable in air and can be synthesized in an air environment. In this study, we attempt to incorporate Cs2SnI6 perovskite into N-719 dye solution in order to increase photon absorbance and to enhance electron transport regarding to enhance the performance of DSSC. In our experiment, Cs2SnI6 was successfully synthesized chemically at room temperature by mixing cesium carbonate (Cs2CO3) into of hydroiodic acid (HI) as a solvent and stannic iodide (SnI4) in warm ethanol to form a precipitate. The absorbance spectra of Cs2SnI6 perovskite show two specific peaks at wavelength of 293 nm and 362 nm. The energy band gap obtained by the Tauc-Plot method is about 3.1 eV. The performance of our fabricated DSSC device was done by J-V measurement. In our experiment, the addition of 7.246 wt% of Cs2SnI6 perovskite solution into dye solution as active material in the DSSC structure reveals the highest power conversion efficiency (PCE) value of 3.97% in comparison to reference device about 1.56%. By using a mixture of GBL-acetonitrile as Cs2SnI6 solvent, the PCE value is more stable than ethanol. For the case of the use GBL-acetonitrile, the PCE value reduce from 3.97% in the 1st week to 3.27% in the 11th week while for ethanol the PCE value was drastically reduced from 4.03% in the 1st week to 1.07% in the 9th week.